2016
DOI: 10.1007/s11130-016-0537-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wheat Dietary Fiber Particle Size during Digestion In Vitro on Bile Acid, Faecal Bacteria and Short-Chain Fatty Acid Content

Abstract: The influence of bile acid concentration on the growth of Bifidobacterium spp. and Lactobacillus spp. bacteria was demonstrated. Exposing these bacteria to the environment containing bile acid salts, and very poor in nutrients, leads to the disappearance of these microorganisms due to the toxic effect of bile acids. A multidimensional analysis of data in the form of principal component analysis indicated that lactic acid bacteria bind bile acids and show antagonistic effect on E. coli spp. bacteria. The growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…The digestive process (30 g of sample) was carried out according to Dziedzic et al ( 2015 ; 2016 ) The size of the reaction tank was modified (1 L). The environment of the stomach, small and large intestine was reproduced as closely as possible (Ulleberg et al, 2011 ) with its pH and enzymes i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The digestive process (30 g of sample) was carried out according to Dziedzic et al ( 2015 ; 2016 ) The size of the reaction tank was modified (1 L). The environment of the stomach, small and large intestine was reproduced as closely as possible (Ulleberg et al, 2011 ) with its pH and enzymes i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The content of TDF, soluble dietary fiber (SDF) and insoluble dietary fiber (IDF) was analyzed using the enzymatic method (Dziedzic et al, 2016 ). The following enzymes were used: thermostable α-amylase (Termamyl 120 L, pH 6.0, 90 °C, 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that long-term intake of wheat bran induces SCFA production and inhibits colon carcinogenesis in mice (for 33 weeks), and reduces the risk of diabetes in rats (16 weeks) (Takahashi et al, 1999;Numan and Rabah, 2015). Other studies have shown that SCFA production is increased in vitro by fermentation of fecal bacteria using wheat bran with smaller-size particle (90 μm of diameter) rather than larger-size particle (500 μm) (Dziedzic et al, 2016), but no such production was observed in the cases of particle sizes of 551 μm and 1,239 μm in vitro (Stewart and Slavin, 2009). However, the benefits of shortterm intake of wheat bran and the in vivo effects of particle-size differences remain unclear.…”
Section: Introductionmentioning
confidence: 98%